Evaluation of the Efficacy of Ethanolic leaf extract of Vernonia amygdalina on the oviposition, egg hatchability and adult emergence of Callosobruchus maculatus(f.) on treated Cowpea seed - Alkali, Z. D.; Abdullahi, N. (UMYU Journal of Microbiology Research)
The efficacy of Vernonia amygdalina ethanolic leaf extract against the oviposition, egg hatchability and adult emergence of Callosobruchus maculatus (F.) on cowpea treated seed was evaluated at the New Biology Laboratory, Department of Science Laboratory Technology, Kano State Polytechnic. Leaf extract from V. amygdalina was obtained by Soxhlet extraction method. maculates were obtained along with infested cowpea grains from Dawanau market in Kano State of Nigeria. The insects were reared in the laboratory and four different concentrations of the leaf extract (1.0, 1.5, 2.0, and 2.5g) were separately mixed with twenty gram (20g) of cowpea in separate Petri-dishes which correspond to (5.0, 7.5, 10, and 12.5 w/w %) respectively. Control treatment was also set along. Five (5) adult pairs of newly emerged C. maculatus were introduced into each Petri dish. Oviposition and egg hatchability of the female insect was significantly reduced on seed treated with higher treatment level (10.0 and 12.5 % w/w) of the extract at (p< 0.05), in comparison with the control treatments. C. maculates adult emergence from seed with varying dose of V. amygdalina was significantly reduced (p < 0 .0 5) compared to other treatments. V. amygdalina plant leaf extract recorded low oviposition (3.3±0.10), low eggs hatchability (0.33±0.19) and lower F1 progeny adult emergence (0.00±0.00),when compared with untreated control treatment (P < 0.05).Therefore the plant has shown a strong effectiveness similar to that of synthetic insecticide in the preservation of cowpea seeds against C. maculatus during storage. It was recommended that government should encourage more planting of these plants that possess insecticidal properties.